2008
DOI: 10.2967/jnumed.108.054023
|View full text |Cite
|
Sign up to set email alerts
|

Use of Adrenomedullin Derivatives for Molecular Imaging of Pulmonary Circulation

Abstract: Currently, there is no low-molecular-weight agent for imaging of the pulmonary circulation. Adrenomedullin (AM) is a peptide predominantly cleared by the pulmonary circulation through specific endothelial receptors. We developed human AM derivatives radiolabeled with 99m Tc and evaluated their biodistribution, plasma kinetics, and utility as pulmonary vascular imaging agents. Methods: Two derivatives radiolabeled with 99m Tc were evaluated: the natural cyclic form of the peptide, to which the chelator diethyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
(24 reference statements)
1
13
0
Order By: Relevance
“…We previously showed that the linear AM peptide, once labeled with 99m Tc, was an attractive lung imaging agent for the diagnosis of pulmonary embolism (5). Lung perfusion scintigraphy with 99m Tclabeled macroaggregates of albumin ( 99m Tc-MAA) is generally con- sidered to be the method of choice for the diagnosis of pulmonary embolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously showed that the linear AM peptide, once labeled with 99m Tc, was an attractive lung imaging agent for the diagnosis of pulmonary embolism (5). Lung perfusion scintigraphy with 99m Tclabeled macroaggregates of albumin ( 99m Tc-MAA) is generally con- sidered to be the method of choice for the diagnosis of pulmonary embolism.…”
Section: Discussionmentioning
confidence: 99%
“…Linear AM was radiolabeled through its cysteine residues as previously described (5). For AM analogs containing a chelating moiety, 2.29 nmol of lyophilized peptide were suspended in 20 mL of 1 M acetate buffer (pH 5.5), to which 200 mL of 0.1 M Na 3 PO 4 (pH 12) and 31.25 mL of freshly prepared SnCl 2 solution (0.8 mg/mL, in 0.05 M HCl) were added.…”
Section: M Tc Labelingmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that PAH would be associated with reduced density of adrenomedullin receptors, which could be measured using an externally detectable tagged receptor substrate. To that aim, we developed a linear human adrenomedullin derivative enabling direct labeling with 99m Tc ( 99m Tc-AM-L) and recently demonstrated the capacity of this agent to specifically bind to lung adrenomedullin receptors, thus enabling the imaging of pulmonary circulation and the detection of large perfusion defects (6). We also demonstrated that linear adrenomedullin specifically binds to human MCF-7 cells expressing adrenomedullin receptors (6).…”
mentioning
confidence: 99%
“…To that aim, we developed a linear human adrenomedullin derivative enabling direct labeling with 99m Tc ( 99m Tc-AM-L) and recently demonstrated the capacity of this agent to specifically bind to lung adrenomedullin receptors, thus enabling the imaging of pulmonary circulation and the detection of large perfusion defects (6). We also demonstrated that linear adrenomedullin specifically binds to human MCF-7 cells expressing adrenomedullin receptors (6). The rat lungs contained a high density of specific adrenomedullin binding sites (dissociation constant, 0.66 nM; maximum number of binding sites, 1,760 fmol/mg protein) (7).…”
mentioning
confidence: 99%